Investigating Undergraduates’ Perceptions on Employability Skills in the UAE: an Analytic hierarchy Process Model in Engineering and Business Students - Khamis AlKhemeiri, Ahmed; Khalid, Khalizani (International Journal of Engineering and Technology, 2018)
This study aims to provide a platform of undergraduatesâ€™ employability skills in non-Western context, specifically, in the UAE. Undergraduates who have completed 90 credit hours of the courses in bachelor studies from business and engineering colleges was randomly sampled in the biggest private university in Abu Dhabi. Questionnaires were distributed with an explanation of the purpose of the elements in the questionnaire to propose an AHP model for employability skills. Consistent with prior studies, communication skills, teamwork, problem solving, and technology was found to be significant and are considered as the upmost important employability skills for business and engineering undergraduates. The significant of the study is also discussed.Â Â Â